The Impact of Ownership Structure on Tax Avoidance: Audit Quality as Moderating Variable - Estetika Mutiaranisa Kurniawati; Siti Rokhimah (Jurnal Akuntansi Aktual, 2024)
Purpose: This research is aimed at giving empirical evidence related to the correlation of ownership and corporate tax avoidance as well as describing the moderating effect of audit quality.Method: The sample comprises 315 observations from manufacturing companies listed on the IDX (Indonesia Stock Exchange) during the period of 2015-2019. For data analysis, panel data regression techniques were employed to ascertain the effect of ownership on tax avoidance moderated by audit quality.Findings: The results indicated that institutional, family, and foreign ownership were positively related to corporate tax avoidance. Nevertheless, the effect of audit quality was found to moderate the correlation of family and foreign ownership to tax avoidance.  Originality/Value: This research contributed fresh evidence that elevated external audit quality held a moderating effect on tax avoidance in family-owned companies and those under foreign ownership.